Women's sexual and reproductive health in war and conflict: are we seeing the full picture? - Jenny Hedström; Tobias Herder (Taylor & Francis Group, 2023)
It is well established that women's sexual and reproductive health (SRHR) is negatively affected by war. While global health research often emphasises infrastructure and systematic factors as key impediments to women's SRHR in war and postwar contexts, reports from different armed conflicts indicate that women's reproduction may be controlled both by state and other armed actors, limiting women's choices and access to maternal and reproductive health care even when these are available. In addition, it is important to examine and trace disparities in sexual reproductive health access and uptake within different types of wars, recognising gendered differences in war and postwar contexts. Adding feminist perspectives on war to global health research explanations of how war affects women's sexual and reproductive health might then contribute to further understanding the complexity of the different gendered effects war and armed conflicts have on women's sexual and reproductive health.